Consumer Trust in Digital Marketing: A Systematic Literature Review and Conceptual Framework - Hasan, Samsurijal; Mayr, Alexander (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This systematic literature review aims to synthesize existing research on consumer trust in digital marketing contexts, identify key determinants and outcomes of trust, and develop an integrative conceptual framework that advances theoretical understanding and practical applications in digital marketing environments. Materials and methods: A comprehensive systematic literature review was conducted following PRISMA guidelines. Electronic databases including Web of Science, Scopus, ScienceDirect, and EBSCOhost were systematically searched for peer-reviewed articles published between 2014 and 2024. The search protocol utilized keywords: